ANALISIS KOMPARASI RASIO KAPASITAS KOLOM GEDUNG BERTINGKAT RENDAH PADA 23 KABUPATEN DI PROVINSI ACEH BERDASARKAN SNI 03-1726-2002 DAN SNI 03-1726-2012 - Fakhrurrazi Fakhrurrazi; Taufik Saidi; Muttaqin Muttaqin (Prodi Magister Teknik Sipil Unsyiah, 2018)
In 2002, through the national standardization agency, the Indonesian government issued SNI 03-1726-2002 on Earthquake Resilience Planning Standard for Building Structure to anticipate the effects of earthquake on building. However, after the standard has been issued there have been several other major earthquakes that rendered it necessary to revise the existing standards. Therefore, in 2012 the government issued SNI 03-1726-2012 on Procedures for Earthquake Resistance Planning for Building and Non Building Structures. When viewed from both these standards, it can be seen that Aceh province is one of the provinces with high earthquake intensity so it is necessary to do a research to observe the effect of changes of both standards to the ratio of column capacity and minimum reinforcement requirements for buildings constructed in Aceh province. Based on the results of the research, the average column capacity ratio against the load in SNI 03-1726-2012 has increased by 45.02% and the average minimum reinforcement requirement available is only 54.5%. The increase is due to an increase in primacy factor from 1.0 to 1.5, causing increased structural load. In addition, there was an increase in the combined burden in the form of 30% additional redundant factors as well as the addition of earthquake load due to an increase in rock bed acceleration factors in some regencies. Thus it can be concluded that the building under review has not fulfilled the requirements of SNI 03-1726-2012 and is recommended for planning by adding a shear wall to reduce the structural load.